PENGARUH KETERAMPILAN BERTANYA GURU TERHADAP KEAKTIFAN BELAJAR SANTRIWAN DAN SANTRIWATI PADA MATA PELAJARAN SKI DI MDTA MUHAJIRIN KAMPUNG BARU GUNUNG TOAR - Rebi Sartika; Bustanur Bustanur; Sopiatun Nahwiyah (Universitas Islam Kuantan Singingi, 2023)
The SKI teacher at MDTA Muhajirin Kampung Baru has implemented good questioning skills, but there are still students and female students who are not active. Based on these problems, this study aims to determine the effect of the teacher’s questioning skills on the learning activeness of students and female students in SKI subjects at MDTA Muhajirin Kampung Baru Gunung Toar. Type this research is a causal associative quantitative study, Total population in this study are all 102 students and female students and random sampling (random sampling) with a total sample of 50 students and female students. The data collection technique used is a questionnaire with instruments in the from of questionnaires, interviews, and documentation. Data analysis used a simple linear regression formula which was processed using SPSS 21.0 software. The results showed that there was a positive and significant effect of the teacher’s questioning skills on the learning activeness of students and female students, the significance test found the equation that the value (sig) was 0,001 < 0,05 so it was concluded that there was an effect of variable X on variabel Y by 22%, while the rest is influenced by other variables.